Canada’s Progressive Trade Agenda and a Free Trade Agreement with China: Are They Incompatible? - Hugh Stephens (The School of Public Policy Publications, 2018)
Negotiating a free trade agreement (FTA) with China will be very different from negotiating one with a country that shares Canada’s Western values. However, an FTA with China makes good economic sense, and while there are some unique obstacles to reaching such an agreement, they are not insurmountable. In fact, Canada can use the same models in negotiating with China that it has used with Western countries. Such an approach combines trade goals with respecting Chinese cultural and political differences, particularly those that fall into the category of progressivism. This category includes labour rights, Indigenous and gender issues, and governance.